Quality with equity : the primary education agenda - Ahmed, Manzoor, 1940-; Nath, Samir R.; Hossain, Altaf (Md. Altaf); Kabir, Mahbubul; Kalam, Abul; Shahjamal, Mirja M.; Yasmin, Rosie Nilufar; Zafar, Tata (Campaign for Popular Education, Bangladesh, 2005)
In the Bangladesh context.